2007
DOI: 10.1007/s10461-007-9247-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Housing Assistance in Four U.S. Cities: Variations in Local Experience

Abstract: This paper provides an account of how young, HIV-positive women manage their lives on limited budgets in four United States cities: New York City, New Orleans, Miami, and Chicago. The study findings elucidate city-to-city variability in housing assistance, and how this manifests in locality specific differences in the experience of HIV. Our research suggests that the receipt of housing assistance has ramifications for women's engagement in care, and for their health. Women not receiving aid often move frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…We also suggest that several environmental aspects of homelessness, such as lacking a space to safely store medication, might have an effect, as could the need for homeless individuals to prioritize immediate survival over the secondary demands of medication adherence. 45,46 Our results do not contradict previous authors 45,47 who have observed that homeless individuals, given adequate adherence, can benefit from ART at levels similar to nonhomeless individuals.…”
Section: Discussionsupporting
confidence: 70%
“…We also suggest that several environmental aspects of homelessness, such as lacking a space to safely store medication, might have an effect, as could the need for homeless individuals to prioritize immediate survival over the secondary demands of medication adherence. 45,46 Our results do not contradict previous authors 45,47 who have observed that homeless individuals, given adequate adherence, can benefit from ART at levels similar to nonhomeless individuals.…”
Section: Discussionsupporting
confidence: 70%
“…Findings reported in this issue show that housing assistance enables low income persons to both preserve and establish stable housing (Dasinger and Speiglman 2007;Scott et al 2007). New HOPWA reporting tools show that homeless and unstably housed program recipients achieve high levels of stability at relatively low per-unit costs: 89% of households receiving average rental assistance of $3,750 were stably housed at one year, as were 79% of residents of supportive housing at an average annual cost of $9,000 (HUD 2006).…”
Section: A Data-driven Hiv/aids Housing Policy Agendamentioning
confidence: 99%
“…Furthermore, housing is multidimensional and many individuals experience different forms of housing instability that increase their risk for multiple health threats (Scott et al 2007;Weir et al 2007). Many at-risk members of this population may not be reached through programs that only provide shelter or other forms of assistance to those who are currently living on the street.…”
mentioning
confidence: 99%